2002
DOI: 10.2214/ajr.178.3.1780673
|View full text |Cite
|
Sign up to set email alerts
|

One Operation After Percutaneous Diagnosis of Nonpalpable Breast Cancer

Abstract: One operation was performed in 80.9% of women with percutaneously proven nonpalpable breast cancer, including 74.1% of women who had breast-conserving surgery and 95.5% of women who had mastectomy. Among women who had breast conservation, one operation was significantly more likely if histologic underestimation was absent or if a mammographic mass was present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Lesions diagnosed as DCIS on needle biopsy and unsuspected invasive carcinoma at surgery result in delayed lymph node biopsies. Thus, patients may have to undergo two separate surgical procedures: one procedure for excision of the lesion and an additional procedure for axillary lymph node evaluation [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Lesions diagnosed as DCIS on needle biopsy and unsuspected invasive carcinoma at surgery result in delayed lymph node biopsies. Thus, patients may have to undergo two separate surgical procedures: one procedure for excision of the lesion and an additional procedure for axillary lymph node evaluation [16]. …”
Section: Discussionmentioning
confidence: 99%
“…12 The accurate percutaneous diagnosis of breast cancer facilitates preoperative planning, often enabling surgical treatment of breast cancer in one operation. 13,14 Previous reports of image-guided large-core needle biopsy (LCNB), mostly using a prone stereotactic guidance technique, have shown that the procedure's accuracy is similar to that of surgical excision. [1][2][3][4][5][6][15][16][17] Sonographically guided Abbreviations: Ca, Carcinoma; DCIS, ductal carcinoma in situ.…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously, there are advantages to proceeding with an image-guided percutaneous needle biopsy as the initial diagnostic strategy. Patients whose diagnosis pf cancer has been made by needle biopsy are more likely to have successful breast-conservation therapy and to require fewer re-excisions for margin control than patients who undergo an initial open biopsy for diagnostic purposes [72]. A core-needle biopsy is preferable to a fine-needle aspiration biopsy because he larger tissue yield can distinguish in situ from invasive architecture and also because the sampling error with a fine-needle aspiration biopsy can be as high as 30%, compared with only 5% to 10% with a core needle.…”
Section: Sampling Errormentioning
confidence: 99%